Estratégia reprodutiva e a expressão de caracteres sexuais secundários em Serrapinnus heterodon Eigenmann, 1915 (Characidae : Cheirodontinae) - Vieira, Carolina Santos (2014)
Tropical regions are often associated with variations in rainfall and temperature. Scenarios like these influence the life cycles of populations in environments subject to fluctuations in abiotic factors, and are often associated with fish reproduction. The reproductive strategies adopted by the species are closely related to the composition of the environment and the evolutionary history of taxonomic groups, taking into account their adaptive capacities. Species with adults of small size and peculiar reproductive attributes exhibit characteristics of specific reproductive strategies. The development of secondary sexual characteristics complements the complexity of reproductive patterns displayed among the groups. Cheirodontinae are abundant in lentic ecosystems and river banks, with species mostly with small size, which includes Serrapinnus heterodon. The present study intended to evaluate the reproductive strategy and the expression of secondary sexual characters in S. heterodon. Specimens of S. heterodon (n=2916, 431 females and 432 males analyzed) were collected between April/2012 and March/2014 in Poxim river, São Cristóvão (SE). Reproductive individuals were found throughout the study period, with minimum sizes of 24.36mm (females) and 22.61mm (males). The reproductive strategy of the species was characterized as opportunistic. The relationship between reproductive rates and the months of the study period showed significant differences (Females: GSI - H=212.5; HSI - H=114, K: H=268.2, p<0.05; Males: GSI - H=124, HSI - H=81.46, K - H=223.9, p<0.05). Absolute fecundity was estimated at 496.18±64.77 oocytes and the relative fecundity at 0.23±0.04 oocytes per mg, and vitellogenic oocytes with 378.35±5.54 m diameter. Significant differences existed between the GSI and the rainfall when correlated to females, but non significant regarding males. An annual reproductive peak was observed during the months from April to November. The ventral curvature of the caudal peduncle and gill gland were observed only in adult males. Bony hooks were registered in adult males, as well as in adult females, but at a lower expression. Females in gonadal developing phase (GD) had hooks on the anal fin (iii+4) and pelvic fins (2+5). Females in spawning capable phase (SC) expressed hooks on the anal fin (iii+5) and pelvic fins (2+6). Males in GD exhibited hooks on the anal fin (iii+7) and pelvic fins (ii+7). In males in SC the hooks were found on the anal fin (ii+17) and pelvic fins (ii+7). The expression of hooks (Females: Anal fin - r=0.42; Pelvic fins - r=0.22, p<0.05; Males: Anal fin - r=0.64; Pelvic fins - r=0.51, p<0.05) and gill gland (W=5123, p<0.05) showed significant values when compared to the GSI.